The Sports Narrative: Phenomenology and Deep Structures of Meaning - Secondulfo, Domenico (Italian Sociological Review, 2022)
The essay takes into consideration some types of sporting events intended as narratives, and analyzes their meaning structures trying to identify some archetypes that could be at the basis of their strong meaning and social impact.